Electrocatalytic activity enhancement of a graphene ink-coated carbon cloth cathode for oxidative treatment. (20th December 2016) - Mousset, Emmanuel; Ko, Zheng Teng; Syafiq, Muhammad; Wang, Zuxin; Lefebvre, Olivier
Graphical abstract: Highlights: Graphene was produced by electrochemical exfoliation instead of chemical method. Graphene increased the surface and conductivity of a raw carbon cloth cathode. Graphene ink-coated carbon cloth was more energy-efficient than uncoated cloth. Electrochemical graphene led to a more energy-efficient cathode than rGO. Abstract: A new graphene-based cathode for electro-Fenton (EF) treatment of wastewater was developed by graphene-ink coating on carbon cloth. Electrochemical exfoliation led to graphene sheet resistance 6-fold lower than a conventional chemical method, an improvement which was attributed to the higher purity of exfoliated graphene as compared to reduced graphene oxide (rGO). Electrochemically-exfoliated graphene was then used as the functional material in the ink-coating process with Nafion as binder and dispersant, and carbon cloth as substrate. The optimized concentration of Nafion and graphene was found to be 0.025% (w/v) and 1.0 mg mL −1, respectively, with a graphene loading equivalent to 0.27 mg cm −2 . Through cyclic voltammetry and electrochemical impedance spectroscopy, the graphene-coated carbon cloth was found to have a 1007% higher electroactive surface (6.31 against 0.57 cm 2 ) and a 97% lower charge transfer resistance (2.45 against 81.08 Ω) than the raw material, leading to improved oxygen reduction reaction (ORR). These enhancements were validated by a near doubling of the maximum electrogenerated H2 O2 yield (2.81 vs 1.43 mg-H2 O2 L −1 cm −2 ), a 3.08-fold increase in the rate of phenol degradation, higher pseudo-first-order rate constants (0.0157 against 0.0051 min −1 ), and a significantly higher mineralization yield (56.6% against 41.2%), after 8 h of EF treatment of 1.4 mmol L −1 of phenol, as compared to uncoated carbon cloth. These improvements were attributed to (i) the outstanding electrical conductivity and exceptionally high specific surface area of the deposited graphene and (ii) the binding and wetting properties of the polytetrafluoroethylene (PTFE)-treated raw carbon cloth itself, thus proving the effectiveness of this modification process. The new graphene-based electrode displayed promising properties for future industrial application of EF treatment of wastewater.